Mitos Memasukkan Sendok ke Dalam Mulut: Tinjauan Literatur Tentang Praktik Pertolongan Pertama Pada Pasien Kejang - Rini Damayanti; Shindy Gustarina; Dina Indrati DS (Universitas Pahlawan Tuanku Tambusai, 2026)
Febrile seizures are one of the most common neurological disorders in children aged 6 months to 5 years and often cause anxiety in families because they occur suddenly and require immediate treatment. Most seizures occur at home, so families play a crucial role in providing first aid to prevent complications such as injury, aspiration, or respiratory distress. However, various studies have shown that public knowledge regarding first aid for seizures is still limited and often influenced by myths that are inconsistent with medical recommendations, such as inserting objects into the patient's mouth during a seizure. This study aims to analyze first aid practices for seizure patients related to the myth of inserting a spoon into the mouth based on a literature review. The method used was a literature review with a narrative analysis approach to various scientific articles discussing family experiences, community knowledge, and first aid practices for patients with seizures or epilepsy. The results of the study indicate that family experiences in providing first aid to children with febrile seizures can be categorized into several main themes: allowing the seizure to continue, observing the child's condition, inserting objects into the child's mouth, and asking for help from others. Some practices carried out by families are still inconsistent with medical recommendations due to limited knowledge and prevailing beliefs in the community. Therefore, a systematic health education program is needed to increase the knowledge and preparedness of families in providing first aid for febrile seizures appropriately and safely.